Manajemen Pemerintahan Desa Sirnabaya Dalam Meningkatkan Produktivitas Unggulan Bumdesa Jayabaya - Nita Yulia Hasanah; Rahmat Hidayah; Rudyk Nababan (Jurnal Ilmiah Wahana Pendidikan, 2022)
The establishment of regional autonomy was enough to bring about changes in various aspects of life. The promulgation of Law No. 23 2014 on regional government, in principle, regulating the management of regional governments, giving priority to the implementation of the principle of decentralization, in which regions have the freedom to operate and take charge of the affairs of government. Government has functions such as service, empowerment and development. The villages of felony network units have obstacles isolating the vicinity to harmonize and manipulate the pursuits of the network there. Thus, the village authorities has Village Owned Enterprises (BUMDes), A company in which the village is wholly or largely owned by having the assets of separate villages directly participate in management. Wealth management, provision and various efforts for the well-being of the village network. The purpose of the researcher is to apply this approach to explain and recognize extra deeply and deeply the authorities control of Sinarbaya village a good way to growth the productiveness of BUMDes in Jayabaya village